PENDIDIKAN INKLUSI SEBAGAI IMPLEMENTASI NILAI-NILAI KARAKTER BANGSA - Nurfatah, Nurfatah; Arafat, Yasir (Graduate Program Magister Manajemen Pendidikan, 2017)
This study aimed at exploring the implementation of the nations character values in relation to the implementation of inclusive education in SD Negeri 8 Talang Kelapa. Currently the moral crisis occured in various countries and also in Indonesia. It need to strengthen character education to overcome this problem. Education in Indonesia also aimed at shaping the human character of Indonesia to be well manifested with the behavior and attitude of living in accordance with the soul of Pancasila. This nation will progress if its education is able to change the character of the nation that is not good to the noble values of Pancasila. Inclusive education as an education that accommodates students with diverse backgrounds, including those with special needs, and learning together in one class. Inclusive education as an implementation of the nations character values. This research was a qualitative research with case study. This research was conducted in SD Negeri 8 Talang Kelapa Banyuasin. The results showed that inclusion education is able to implement the character values among the prominent ones 1) social care 2) tolerance; 3) independent. Activities in the implementation of character values include learning, habituation, and extra curricular.